The morphotropic phase boundary in the (1 - x)PbZrO3-x[0.3Bi(Zn1/2Ti1/2)O3-0.7PbTiO3] perovskite solid solution - T. Sareein (2018)
Ceramics in the (1 - x)PbZrO3-x[0.3Bi(Zn1/2Ti1/2)O3-0.7PbTiO3] solid solution system with 0.48< x ≤ 0.56 were investigated. A morphotropic phase boundary separating rhombohedral and tetragonal perovskite phases was identified at x = 0.52. This composition displays the maximum remanent polarization Prof 40.7 μC/cm2and the best piezoelectric coefficient d33of 311 pC/N in the pseudobinary system. However, the Curie temperature Tcfor this MPB composition is 291 °C, much lower than initially expected. © Springer Science+Business Media, LLC 2011.